Telaah Yuridis Dan Filosofis Sistem Pendidikan Diniyah pada Tingkat Menengah (Wustha) dan Tingkat Lanjutan (Ulya);: Berdasarkan Undang-Undang Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional - Suwandi Suwandi; Ubaid Ridlo; Raswan Raswan (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
This study aims to strengthen the normative and philosophical foundations of Pendidikan Diniyah Formal at the Wustha and Ulya levels in Indonesia as an effort to align the pesantren system with the national education framework. Within the scope of Law No. 20 of 2003 on the National Education System, Pendidikan Diniyah Formal holds a strategic role as both a legally recognized Islamic institution and a center for spiritual and moral development. Using a qualitative descriptive method through literature review, this study examines educational regulations, legal frameworks, and scholarly works related to pesantren and Arabic Language education. The analysis explores the interconnection between juridical legitimacy and philosophical principles in the formulation of the Pendidikan Diniyah Formal curriculum. Findings show that the curriculum is supported by a strong legal basis (Law No. 20/2003, PP No. 55/2007, PMA No. 13/2014, and Law No. 18/2019) and grounded in the principle of tafaqquh fi al-din, which integrates religious and general sciences to build student character. Strengthening the Pendidikan Diniyah Formal curriculum through juridical and philosophical approaches is essential to developing inclusive, high-quality, and globally relevant Arabic language education.